Karakozof : eene bladzijde uit de geschiedenis van Rusland. - van der Meij, H. Wolfgang ('s-Gravenhage : Stemberg, 1882)
Collectie Vrijzinnige Werkmansbibliotheek
Nederlands
Monografie
Keywords: Vrijzinnige Werkmansbibliotheek